Coyuntura Económica - Avelino Martínez Sandoval; María Carolina Rozo; Guillermo Aponte Bello; Holmes Sánchez Rengifo; Martha Vázquez Olave; Leidy Ángel Giraldo (Revista de Economía & Administración E-ISSN 2463-1035 ISSN 1794-7561, 2008)
Coyuntura Económica